2010
DOI: 10.1002/14651858.cd006624.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride versus other atypical antipsychotics for schizophrenia

Abstract: Background-In many countries of the industrialised world second generation (atypical) antipsychotics have become first line drug treatments for people with schizophrenia. The question as to whether, and if so how much, the effects of the various second generation antipsychotics differ is a matter of debate. In this review we examine how the efficacy and tolerability of amisulpride differs from that of other second generation antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 87 publications
3
19
0
7
Order By: Relevance
“…Additionally, one included trial [ 18 ] showed no statistical difference between amisulpride and olanzapine groups on relapse rates. These results were consistent with those in previous systematic reviews and meta-analyses [ 11 ]. Other efficacy outcomes such as quality of life (QoL) and general function are also important.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, one included trial [ 18 ] showed no statistical difference between amisulpride and olanzapine groups on relapse rates. These results were consistent with those in previous systematic reviews and meta-analyses [ 11 ]. Other efficacy outcomes such as quality of life (QoL) and general function are also important.…”
Section: Discussionsupporting
confidence: 94%
“…A Cochrane systematic review published in 2010 summarized corresponding clinical outcomes and found that the efficacy of amisulpride was similar to that of olanzapine and risperidone, and better than that of ziprasidone. Amisulpride was likely to be associated with less weight gain than risperidone and olanzapine [ 11 ]. However, the review contained no studies performed on Chinese patients.…”
Section: Introductionmentioning
confidence: 99%
“…25 Previous studies suggested that amisulpride is better in improvement of negative symptoms and it causes fewer extrapyramidal side-effects, weight gain, and specific endocrinological and sexual disorders than risperidone in patients with psychosis. [26][27][28] The selective action at limbic cortical dopamine D2/D3 receptors that cause less severe extrapyramidal side-effects and 5-HT7A receptor antagonism underlying antidepressant actions may contribute to the difference in QoL. 29 Haloperidol and risperidone have higher potency at dopamine D2 receptors than other antipsychotics and they caused more severe extrapyramidal sideeffects in patients with first-episode psychosis despite their relative moderate dosage.…”
Section: Discussionmentioning
confidence: 99%
“…19 Although there are only small and inconsistent differences between different antipsychotics, other than clozapine, with respect to efficacy, there are large differences in adverse effect profiles. [25][26][27][28][29][30] Therefore, the choice of antipsychotic medication is generally made based on previous response to individual antipsychotic medications and relative side effects. 31 If extrapyramidal symptoms, including tardive dyskinesia, are of particular concern to a patient, then second generation or low potency first generation antipsychotics should be used.…”
Section: Treatmentmentioning
confidence: 99%